2011
DOI: 10.1017/jfm.2011.336
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of two-dimensional Faraday waves with phase-field modelling

Abstract: A fully nonlinear numerical simulation of two-dimensional Faraday waves between two incompressible and immiscible fluids is performed by adopting the phase-field method with the Cahn-Hilliard equation due to Jacqmin (J. Comput. Phys., vol. 155, 1999, pp. 96-127). Its validation is checked against the linear theory. In the nonlinear regime, qualitative comparison is made with an earlier vortex-sheet simulation of two dimensional Faraday waves by Wright , Yon & Pozrikidis (J. successfully simulated with the pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 24 publications
1
29
0
Order By: Relevance
“…They perform analyses in two and three dimensions and their results for the threshold values of the oscillating acceleration amplitude are in good agreement with the Floquet analysis of Kumar and Tuckerman [2]. In order to validate the numerical results of Périnet et al [14] with a different numerical method, Takagi and Matsumoto [15] use a numerical scheme based on the phase-field method. They perform an analysis for both linear and nonlinear regimes.…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…They perform analyses in two and three dimensions and their results for the threshold values of the oscillating acceleration amplitude are in good agreement with the Floquet analysis of Kumar and Tuckerman [2]. In order to validate the numerical results of Périnet et al [14] with a different numerical method, Takagi and Matsumoto [15] use a numerical scheme based on the phase-field method. They perform an analysis for both linear and nonlinear regimes.…”
Section: Introductionsupporting
confidence: 53%
“…Their results for the magnitude of the critical acceleration in the linear regimes are in good agreement with those of Périnet et al [14], but, in the nonlinear regime, the comparison of the interface dynamics in their test case, taken from Wright et al [7], is only qualitative due to differences between properties of fluids (densities), the size of the physical domain, and the consideration of viscous effects. Takagi and Matsumoto [15] show that the trends of the interface dynamics is similar in both methods and conclude that their model is able to provide accurate numerical results of the Faraday instability. Other different nonlinear cases are tested and show good agreement with experimental results of Jiang et al [16], in particular, concerning the occurrence of the period tripling of standing waves.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…In their numerical simulations and after about ten subharmonic periods, P erinet et al [365] predicted a drastic departure from hexagonal symmetry. A fully nonlinear numerical simulation of 2D Faraday waves between two incompressible and immiscible fluids was performed by Takagi and Matsumoto [367] who adopted the phase-field method developed originally by Jacqmin [368]. In the nonlinear regime, qualitative comparison was made with an earlier vortex-sheet simulation of two-dimensional Faraday waves by Wright et al [21].…”
Section: Three-and Multifrequency Parametric Excitationmentioning
confidence: 99%
“…The parametric instability analysis for the interface of two viscous fluids was studied by Kumar and Tuckerman [7], who found that the effect of large viscosity on the wavelength selection is substantial. The two-dimensional Faraday waves of two inviscid fluids were numerically studied by Wright et al [8], the results were also compared with the fully nonlinear numerical simulation by Takagi and Matusumoto [9]. The instability of Faraday interfacial waves between two weakly viscous layers in a rectangular domain was studied by Hill [10].…”
Section: Introductionmentioning
confidence: 99%